Screening of Pleurotus ostreatus isolates for their ligninolytic properties during cultivation on natural substrates - Eichlerová, I; Homolka, L; Nerud, F; Zadrazil, F; Baldrian, P; Gabriel, J (Biodegradation, 2000)
Thirteen basidiospore-derived isolates of Pleurotus ostreatus f6 strain differing in the level of ligninolytic enzyme production and other characteristics (mycelium extension rate, colony morphology) from the parental strain were cultivated on natural substrates. Under these conditions ligninolytic enzyme activity, loss of organic mass, polycyclic aromatic hydrocarbons (PAHs) degradation and colonization of sterile and nonsterile soil were studied. The activity of ligninolytic enzymes was substantially higher in straw than in liquid culture, although the differences between the isolates were less pronounced on this substrate. Some of the isolates showed a very good ability to decompose the lignocellulosic substrate (straw) and a relatively high loss of organic mass was found after 50 days of cultivation in these strains. The original strain f6 and isolates B13 and B26 successfully degraded all seven tested PAH compounds present in experimental soil samples, but the higher or lower ligninolytic enzyme production of isolates tested had no substantial effect on the extent of the degradation. In our screening, six basidiospore-derived isolates growing well in nonsterile soil were found, which could be suitable for the prospective biotechnological exploitation.
Keywords: polycyklické aromatické uhlovodíky; lignin; Cell Division; Substrate Specificity; biodegradace; Peroxidases; pšenice; Polycyclic Aromatic Hydrocarbons; Biodegradation, Environmental; Culture Media; kultivační média; oxidoreduktasy; Lignin; lakasa; substrátová specifita; půdní mikrobiologie; Laccase; Triticum; peroxidasy; Pleurotus; Oxidoreductases; Soil Microbiology; buněčné dělení